2003
DOI: 10.1007/s00122-003-1311-3
|View full text |Cite
|
Sign up to set email alerts
|

The development and evaluation of consensus chloroplast primer pairs that possess highly variable sequence regions in a diverse array of plant taxa

Abstract: Although universal or consensus chloroplast primers are available, they are limited by their number and genomic distribution. Therefore, a set of consensus chloroplast primer pairs for simple sequence repeats (ccSSRs) analysis was constructed from tobacco (Nicotiana tabacum L.) chloroplast sequences. These were then tested for their general utility in the genetic analysis of a diverse array of plant taxa. In order to increase the number of ccSSRs beyond that previously reported, the target sequences for SSR mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 39 publications
0
92
0
2
Order By: Relevance
“…Another marker of the chloroplast genome, the consensus chloroplast SSR marker, ccSSR7 (Chung and Staub, 2003), was used in this study because Tanaka et al (2006) reported that ccSSR7 was polymorphic by deletion of 5 bp (ATATT). The nucleotide sequence of each primer was: ccSSR7-F-5' CGGGAAGGGCTCG KGCAG 3' (K = T or G) and ccSSR7-R-5' GTTCGAAT CCCTCTCTCTCCTTTT 3'.…”
Section: Analysis Of Ps-id and Ccssr7mentioning
confidence: 99%
“…Another marker of the chloroplast genome, the consensus chloroplast SSR marker, ccSSR7 (Chung and Staub, 2003), was used in this study because Tanaka et al (2006) reported that ccSSR7 was polymorphic by deletion of 5 bp (ATATT). The nucleotide sequence of each primer was: ccSSR7-F-5' CGGGAAGGGCTCG KGCAG 3' (K = T or G) and ccSSR7-R-5' GTTCGAAT CCCTCTCTCTCCTTTT 3'.…”
Section: Analysis Of Ps-id and Ccssr7mentioning
confidence: 99%
“…For chloroplast microsatellite analyses, we employed universal primer pairs described to dicotyledonous angiosperms by Weising and Gardner (1999) and Chung and Staub (2003).…”
Section: Amplification and Genotyping Of Chloroplast Microsatellite Locimentioning
confidence: 99%
“…The identification and development of cpSSRs is achieved principally by utilizing the nucleotide sequence information retrieved from public databases (Weising and Gardner, 1999;Chung and Staub, 2003) and also by sequencing PCR products generated by "consensus/universal primers", capable of amplifying cpDNA regions in several species.…”
Section: Chloroplast Ssr Markersmentioning
confidence: 99%
“…Sequencing of amplicons generated by these universal cpDNA-PCR primers provide basic information about mononucleotide tracts and flanking sequences in the amplicons. Since the flanking regions of cpSSR loci are highly conserved, 'universal cpSSR primers' (Weising and Gardner, 1999;Chung and Staub, 2003;Ebert and Peakall, 2009) that enable the amplification of cpSSRs across species/taxa have been identified. Most of the molecular studies involving chloroplast microsatellites now rely on testing these universal cpSSRs in the target species.…”
Section: Chloroplast Ssr Markersmentioning
confidence: 99%